Estimación de potenciales choques traseros utilizando modelos de tiempo para colisión (2011)
AbstractOne of the crucial factors to relieve the potential danger of rear-end collision is to synchronize the behavior of the lead and following vehicle on target lane, which includes the relative speed to the leading vehicle on the target lane and the time headways to both the leading and following vehicles on the target lane as the explanatory variables. In view of the rear-end conflicts importance, here it is tried to find out the critical headway of the vehicles in which vehicles encounter with this kind of Traffic Conflicts, based on Traffic Conflict Technique. It was also aimed at introducing a model to estimate the number of vehicles with rear-end conflict potential on the basis of physical and traffic equations in signalized intersections. Moreover rear-end potential conflicts have been calculated by modeling in MATLAB, then by comparison of the field observation and outcome of the model the accuracy of the model has been estimated.